Evaluating the effectiveness of active programs of employment in the region - Alena Vankevich; Alena Korobova (Vestnik of Vitebsk State Technological University, 2015)
The subject of the study is the effectiveness of active programs of employment. The purpose of this paper is to generalize the existing theoretical concepts determining the effectiveness of employment programs to support the methodological approach to the evaluation of their effectiveness in the region, harmonized with the existing statistical base. Testing of methodical approach (for the region database, the Republic of Belarus) led to the conclusion that despite the priority of active programs to promote employment in the region, they are a quite narrow circle of persons, some of which are not focused on employment. In the database of public service employment is dominated by vacant jobs and vacancies of low quality, but most programs are only of short-term effect. Results of the study to assess the effectiveness of regional employment programs not only in quantity but also in quality, optimize the cost of the state budget for active employment programs, get target employment policies to increase the activity of citizens in job search and job placement.